Hemobilia, an uncommon case in a patient with severe acute cholangitis: a case report - Martinez-Garcia, Erik; Roman-Chávez, Pedro D.; Galván-Ortiz, Marco A.; Figueroa-Zariñana, Víctor H.; Madrid-Ruiz, José F. (International Journal of Research in Medical Sciences, 2024)
Hemobilia is an uncommon cause of upper gastrointestinal bleeding and it is usually associated with hepatobiliary trauma. We present a 71-year-old female patient with type 2 diabetes mellitus and hypertension, who was admitted to the emergency department due to clinical features of a severe acute cholangitis and hemodynamic instability. She required an external drainage through a T-tube in the common bile duct and admission to the intensive care unit in order to improve clinical conditions for a definitive treatment. Afterwards we performed an open cholecystectomy with a satisfactory postsurgical outcome and decided to discharge her. However, she was readmitted due to melena and bleeding through the T-tube, which developed a hypovolemic shock treated with crystalloid fluids and blood transfusion. It is still in discussion what is the best treatment option. Since the objective is to preserve the integrity of the bile duct, only 5% of the cases will require a major intervention. It is important to individualize every case.